The invisible harm: land clearing is an issue of animal welfare - Finn, Hugh; Stephens, N. (2017)
Land clearing is a significant environmental issue in Australia and an area of active legislative reform. Despite evidence of the harm that land clearing causes to individual animals, such harm is either ignored or considered only indirectly in environmental decision-making. We argue that the harm that land clearing causes to animals ought to be identified and evaluated in decision-making relating to land clearing and consider the following three propositions in support: (1) land clearing causes deaths that are physically painful and psychologically distressing because of their traumatic and debilitating nature; (2) land clearing causes physical injuries, other pathological conditions, pain and psychological distress over a prolonged period as animals attempt to survive in the cleared environment or in the environments they are displaced to; and (3) on the basis of current clearing rates, more than 50 million mammals, birds and reptiles are likely to be killed annually because of land clearing in Queensland and New South Wales. The scientific consensus about the harm caused by land clearing means that decisions to allow land clearing are decisions to allow most of the animals present to be killed and, as such, frameworks for decision-making ought to include proper evaluation of the harm to be imposed.